A review of the link between psychological stress and inflammatory bowel disease exacerbation - Annelise Klettner; Shanhong Luo; Laura D. Coyle; Nathan Liu (Academia Mental Health & Well-Being)
Inflammatory bowel disease (IBD) is a chronic relapsing and remitting illness characterized by episodes of inflammation in the gastrointestinal tract. This condition affects several million people worldwide and has become more prevalent in recent decades. It frequently manifests in individuals aged 15–35 and is observed among high school-aged adolescents and college-aged adults. Despite extensive research, the root cause of IBD remains unknown. The largely unknown etiology of the illness, variability of symptoms, and the need for improvement in the efficacy of IBD treatment underscore the significance of psychosocial factors on the influence of the condition. This review examines three lines of stress research—stressful life events, daily stress, and perceived stress—to evaluate the association between psychological stress and IBD exacerbation. A review of empirical evidence shows a robust link between psychological stress and disease activity in IBD, suggesting that psychological stress is a risk factor for disease exacerbation. Four major limitations involving psychological stress in the IBD literature are identified: (1) the influence of daily stress on IBD exacerbation, (2) stress conceptualization and the operationalization of disease activity, (3) directionality between stress and IBD activity, and (4) moderators of the link between stress and disease exacerbation. Future directions for stress research in IBD are proposed.